Characterization of nanocomposite tetrahedral amorphous carbon coated drill bits for improved drilled-hole quality in carbon fiber-reinforced polymer/Al7075-T6 stacks - Joy Mathavan, J.; Hafiz Hassan, M.; Samad Mahmud, A. (Research gate, 2023)
The use of hybrid composite stacks is kept on increasing in the aircraft industry due to their numerous advantages in this sector. Therefore, improving the drilled-hole quality is also sought over time. The present work focuses on the effect of metallic elements-doped tetrahedral amorphous carbon coated drill bits on the drilled-hole quality while performing single- shot drilling of CFRP/Al7075-T6 stacks. This was evaluated from CFRP exit delamination and Al7075-T6 exit burr height. Mechanical and tribological properties of three different tetrahedral amorphous carbon (ta-C) coating-types, i.e. micro-, chromium-doped (:Cr) and titanium-doped (:Ti) were compared to uncoated tool ones. Bonding strength of the selected coatings with the tool was also calculated. Process capability six pack analysis was used to validate the experimental results obtained for drilled-hole quality. It was shown that micro-ta-C coating-type exhibited maximum hardness. The hardness value directly influences the exit delamination. It was found that CFRP exit delamination decreased as the hardness of the drill bit increased. Moreover, the multi-material stacks drilled with ta-C:Cr coated tool presented the lowest burr height (less than 150 μm), compared to the other tested coating-types. Low-friction surfaces seem to promote low exit burr height.
Keywords: Hole edge analysis; Carbon fiber-reinforced polymer/Al7075-T6 stacks panel; Tetrahedral amorphous carbon coated tools; Single-shot drilling; Process capability six pack analysis